Toward real time IoT based paste monitoring system for small to medium enterprise (SME) - Adesta, Erry Yulian Triblas; Hilmy, Irfan; ,, Avicenna; Agusman, D. (IOP Publishing Ltd, 2019)
Quality and consistency of a product have always been the most critical demand in the food paste industry. One of the ways to retain its high standard is through managing consistency. An affordable prototype of the Internet of Things (IoT) based tool used for paste consistency monitoring of various paste property sensors by means of low cost Arduino based embedded system is presented. For a Small and Medium Enterprise (SME), the word „Affordable‟ is a critical term. They could not compete with a big enterprise corporation in term of having a high-end monitoring system. Four paste properties were measured: thickness, color, pH and temperature. The status of all parameters was monitored and displayed in two modes: local LCD screen and remote screen from any Wi-Fi based portable gadget. The inhouse Arduino based scripting code was developed to integrated the system. The result shows that the developed system could be implemented as a local measurement tool and also be monitored remotely as an IoT based system. The measurement system was validated with the manual measurement. The framework to rescale the project into a bigger scale system was also developed in order to make this system ready for the Industrial 4.0 requirement.